The Role of Adiponectin in the Pathogenesis of Metabolic Disturbances in Patients With Schizophrenia - Chen, Cynthia Yi-An; Goh, Kah Kheng; Chen, Chun-Hsin; Lu, Mong-Liang (Frontiers in Psychiatry, 2021)
Antipsychotic-induced metabolic disturbance is a common adverse event occurring in patients treated with antipsychotic drugs. The mechanisms underlying metabolic dysregulation are complex, involving various neurochemical and hormonal systems, the interaction of genetic and lifestyle risk factors, and the antipsychotic drug prescribed. Recently, there has been increasing interest in the relationship between antipsychotic-induced metabolic disturbances and body weight regulatory hormones such as adiponectin. Adiponectin, an adipocyte-derived protein related to insulin sensitivity, weight gain, and anti-inflammation, has attracted great attention because of its potential role of being a biomarker to predict cardiovascular and metabolic diseases. Previous studies regarding the effects of antipsychotics on blood adiponectin levels have shown controversial results. Several factors might contribute to those inconsistent results, including different antipsychotic drugs, duration of antipsychotic exposure, age, sex, and ethnicity. Here we summarize the existing evidence on the link between blood adiponectin levels and metabolic disturbances related to antipsychotic drugs in patients with schizophrenia. We further discuss the effects of individual antipsychotics, patients' gender, ethnicity, age, and treatment duration on those relationships. We propose that olanzapine and clozapine might have a time-dependent biphasic effect on blood adiponectin levels in patients with schizophrenia.